Plasma Metabolic Profiling of Human Thyroid Nodules by Gas Chromatography-Mass Spectrometry (GC-MS)-Based Untargeted Metabolomics - Abooshahab, Raziyeh; Hooshmand, Kourosh; Razavi, S. Adeleh; Gholami, Morteza; Sanoie, Maryam; Hedayati, Mehdi (Frontiers in Cell and Developmental Biology, 2020)
One of the challenges in the diagnostic area of human thyroid cancer is a preoperative diagnosis of thyroid nodules with indeterminate cytology. Herein, we report an untargeted metabolomics analysis to identify circulating thyroid nodules metabolic signatures for finding the new novel metabolic biomarkers. Untargeted gas chromatography-quadrupole-mass spectrometry (GC-Q-MS) was used to ascertain the specific plasma metabolic changes of thyroid nodule patients consisted of papillary thyroid carcinoma (PTC; n = 19), and multinodular goiter (MNG; n = 16) compared to healthy subjects (n=20). Diagnostic models constructed using multivariate analysis such as principal component analysis (PCA), orthogonal partial least squares discriminant analysis (OPLS-DA), and univariate analysis including One-way ANOVA and volcano plot by MetaboAnalyst and SIMCA software. Because of the multiple-testing issue, false discovery rate (FDR) p-values are also computed for this functions. A total of 60 structurally annotated metabolites were subjected to statistical analysis. A combination of univariate and multivariate statistical analyses revealed a panel of metabolites responsible for the discrimination between thyroid nodules and healthy subjects with variable importance in the projection (VIP) value greater than 0.8 and P value less than 0.05. Significantly altered metabolites between thyroid nodules versus healthy persons are those associated with amino acids metabolism, tricarboxylic acid cycle, fatty acids and purine and pyrimidine metabolism, including cysteine, cystine, glutamic acid, α-ketoglutarate, 3-hydroxybutyric acid, adenosine-5-monophosphate and uracil respectively. Further, sucrose metabolism differed profoundly between thyroid nodule patients and healthy subjects. Moreover, according to the receiver operating characteristic (ROC) curve analysis, sucrose could discriminate PTC from MNG (area under ROC curve value = 0.92). This study enhanced our understanding of the distinct metabolic pathways associated with thyroid nodules, which enabled us to distinguish between patients and healthy subjects. In addition, our study showed extensive sucrose metabolism in the plasma of thyroid nodules patients, which provides a new metabolic signature of the thyroid nodules tumorigenesis. Accordingly, it suggests that sucrose can be considered as a circulating biomarker for differential diagnosis between malignancy and benignity in indeterminate thyroid nodules.